Studies on cavitation / Norazilah Dillah and Nor Zaupah Sulima - Dillah, Norazilah; Sulima, Nor Zaupah (Faculty of Mechanical Engineering, 1998)
This work presents the outcome of few studies on cavitation. Case studies are presented to show the cavitation damage in turbines, pumps and propellers. Experimental results are presented using the Universal Axial flow Apparatus running under pump mode and turbine mode. Experimental results using cavitation apparatus are also presented. Formation of cavitation bubbles in the Universal axial Flow Apparatus and the cavitation apparatus are shown. The effects of cavitation on machine members and methods to prevent them are presented.